2016
DOI: 10.1017/s0898588x16000079
|View full text |Cite
|
Sign up to set email alerts
|

Patronage, Logrolls, and “Polarization”: Congressional Parties of the Gilded Age, 1876–1896

Abstract: According to the quantitative indicators scholars use to measure political polarization, the Gilded Age stands out for some of the most party-polarized Congresses of all time. By contrast, historians of the era depict the two major parties as presenting few programmatic alternatives to one another. I argue that a large share of the party-line votes in the Congress of this period are poorly suited to the standard conceptualization as “polarization,” meaning wide divergence on an ideological continuum structurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The tariff and internal improvements especially reflected ideological concerns but related to distributive policies or particularized interests more prominently. As a result, the cause for the debate between the parties on these issues were at times starker than others (Lee 2016). On perhaps the most controversial economic issue of the Gilded Age, the standards debate, however, the parties converge for most of the period.…”
Section: Discussion: Polarization In the 1850s And 1890smentioning
confidence: 99%
See 3 more Smart Citations
“…The tariff and internal improvements especially reflected ideological concerns but related to distributive policies or particularized interests more prominently. As a result, the cause for the debate between the parties on these issues were at times starker than others (Lee 2016). On perhaps the most controversial economic issue of the Gilded Age, the standards debate, however, the parties converge for most of the period.…”
Section: Discussion: Polarization In the 1850s And 1890smentioning
confidence: 99%
“…On perhaps the most controversial economic issue of the Gilded Age, the standards debate, however, the parties converge for most of the period. It appears that neither party seemed to articulate an explicit stance on the matter until the 1890s due to the regional splits within both parties over the money question (Lee 2016; Ritter 1997).…”
Section: Discussion: Polarization In the 1850s And 1890smentioning
confidence: 99%
See 2 more Smart Citations
“…3. While DW-NOMINATE scores are a defensible and widely used measure of legislator ideology, Lee (2016) has recently suggested that NOMINATE taps into party and ideology simultaneously and may yield a measure of ideology extremity even for members who are simply "party regulars." This cautions against interpreting the relationship between NOMINATE scores and bill introductions as a test of how ideological extremity alone affects bill sponsorship behavior.…”
Section: Appendixmentioning
confidence: 99%